Mickey Mouse sign and Humming Bird sign: Diagnostic Clue of Progressive Supranuclear Palsy - Diguvinti sreeramulu; SM Saifullah Quraishi; Harish PV; C Ravi Theja (International Journal of Medical Research and Review, 2014)
Progressive supranuclear palsy is a neurodegenerative disorder. The cause of PSP is unknown. It is under diagnosed by physician and neurologist. Clinical feature of PSP resemble with parkinsonism, carticobasal degeneration, multiple system atrophy and multi infarct state. Due to common clinical feature with Parkinsonism, carticobasal degeneration, multiple system atrophy neuroimaging that can help to diagnose PSP. MRI play pivotal role in confirming the diagnosis.